2016
DOI: 10.1515/jppr-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication. Monitoring the occurrence of bacteria in stored cabbage heads

Abstract: Twenty-six cabbage heads stored under typical conditions in a storage hall in Moravia, Czech Republic, were tested for the presence of bacteria by the method of isolation from three diff erent parts of the cabbage heads. Isolations were carried out from stalks, inner and superfi cial leaves. Two samplings were done; in November 2015 and February 2016. Bacterial cultures were sequenced in the part of 16S rRNA region; bacteria were identifi ed according to the sequences obtained. Th e most prevalent bacteria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Pseudomonas species appeared more on cabbage heads at harvest, however, the bacterial spectrum changed over time in favor of this genus. The decline of other bacterial genera after four months of cold storage was also observed in our previous study [21] and it could be explained by strong antagonistic behavior of Pseudomonas sp. [46] and Bacillus species against other bacteria [47,48].…”
Section: Changes Of Bacterial Spectra Presented In Cabbage Heads Inocsupporting
confidence: 80%
See 2 more Smart Citations
“…Pseudomonas species appeared more on cabbage heads at harvest, however, the bacterial spectrum changed over time in favor of this genus. The decline of other bacterial genera after four months of cold storage was also observed in our previous study [21] and it could be explained by strong antagonistic behavior of Pseudomonas sp. [46] and Bacillus species against other bacteria [47,48].…”
Section: Changes Of Bacterial Spectra Presented In Cabbage Heads Inocsupporting
confidence: 80%
“…In this study, the presence of the B. subtilis group in control heads was similar in both samplings and detection of the B. cereus group decreased markedly after storage. However, in our previous studies, the increase of the latter genus during storage was observed [21]. Species belonging to Bacillus genera are inconsistently reported as food poisoning microorganisms frequently present in cooked and slowly cooled-down food [55,56], while on the other hand some are considered as potential bio-control agents against postharvest pathogens of vegetables and fruits [48,57].…”
Section: Changes Of Bacterial Spectra Presented In Cabbage Heads Inocmentioning
confidence: 78%
See 1 more Smart Citation
“…The Pss pathogen isolated from bronzing jackfruit in Malaysia could affect sweetcorn, pineapple, and cucumber in vitro (Abidin et al 2021). In addition, other Pantoea species are severe pathogens of rice that cause diseases worldwide (Azizi et al 2020), as well as on other crops such as strawberries (Abdel-Gaied et al 2022) in the field and cabbage heads in storage (Eichmeier et al 2017).…”
Section: Introductionmentioning
confidence: 99%